2015
DOI: 10.1002/mrd.22518
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrition influences angiogenesis in the placenta through peroxisome proliferator activated receptors: A novel hypothesis

Abstract: SUMMARYPlacental angiogenesis is critical to maintain adequate blood flow during gestation, and any alterations in this process can result in an adverse pregnancy. Growing evidence indicates that suboptimal maternal nutrition can alter placental development. Although the underlying mechanisms are not clear, maternal nutrition likely influences the expression of genes involved in placental development through regulation of various transcription factors such as peroxisome proliferator-activated receptors (PPARs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 95 publications
(107 reference statements)
0
27
0
Order By: Relevance
“…VEGF, acting as a key angiogenesis promoter, plays a significant role in physiological and pathophysiological vascular development and maintenance 23 . It has been shown that VEGF expression is found in the decidua cells of early pregnancy, and it participates in physiological placental angiogenesis during embryogenesis and reproductive functions during the initial stages of pregnancy 24 . Dysregulation of VEGF expression has been linked to the onset of placental pathologies including preeclampsia, early pregnancy loss and intrauterine growth restriction and is deeply implicated in multiple steps of RSA occurrence and development 25 26 .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF, acting as a key angiogenesis promoter, plays a significant role in physiological and pathophysiological vascular development and maintenance 23 . It has been shown that VEGF expression is found in the decidua cells of early pregnancy, and it participates in physiological placental angiogenesis during embryogenesis and reproductive functions during the initial stages of pregnancy 24 . Dysregulation of VEGF expression has been linked to the onset of placental pathologies including preeclampsia, early pregnancy loss and intrauterine growth restriction and is deeply implicated in multiple steps of RSA occurrence and development 25 26 .…”
Section: Discussionmentioning
confidence: 99%
“…PPARs are nuclear transcription factor and nutrient-sensing signaling that regulate metabolic and tissue developmental processes. Studies focusing on the mechanisms of such metabolic programming have implicated PPARs as a candidate gatekeeper pathway of developmental programming [ 21 , 22 , 23 ], although their relationship with programmed hypertension and metabolic syndrome remains to be established.…”
Section: The Impact Of Renal Programming In Programmed Hypertensiomentioning
confidence: 99%
“…Obesity in pregnancy has been associated with an increased risk of metabolic disorders and adverse pregnancy outcomes, including gestational diabetes mellitus (GDM), gestational hypertension, preeclampsia, and preterm delivery . The placenta is the organ responsible for mammalian embryo survival.…”
Section: Introductionmentioning
confidence: 99%